2022
DOI: 10.3390/polym14040794
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition Coating Based on the Self-Assembled Polydopamine Films and Its Anti-Corrosion Properties

Abstract: Metal corrosion is becoming increasingly serious in oil and gas production, and one way to solve this problem is to modify the metal surface. Thus, a corrosion inhibition coating on the N80 steel was constructed via the self-polymerization and assembling of the dopamine. The optimum reaction condition of polydopamine films was determined by the corrosion rate assessment of the films coated N80 steel, which was the reaction at 60 °C and 5 g/L dopamine in the Tris-HCl buffer solution (pH = 8.5) for 1 h. The spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As an important group of scale inhibitors, most polymeric inhibitors contain little or no phosphorus element, making these materials substantially more environmentally friendly compared with aminophosphonates. Thus many polymeric inhibitors are regarded as “green inhibitors” [ 4 , 5 , 22 , 23 ]. Moreover, due to the versatile molecular structures of polymeric inhibitors, many polymeric inhibitors have unique advantages over aminophosphonates, such as a higher calcium tolerance, higher thermal stability, and a wider range of pH tolerance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an important group of scale inhibitors, most polymeric inhibitors contain little or no phosphorus element, making these materials substantially more environmentally friendly compared with aminophosphonates. Thus many polymeric inhibitors are regarded as “green inhibitors” [ 4 , 5 , 22 , 23 ]. Moreover, due to the versatile molecular structures of polymeric inhibitors, many polymeric inhibitors have unique advantages over aminophosphonates, such as a higher calcium tolerance, higher thermal stability, and a wider range of pH tolerance [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As exhibited in Figure a, an obvious peak centered at 1635 cm –1 was detected for all samples, assigning to absorbed moisture. Beneath pure EP, the main components of corrosion products were γ-FeOOH (1020 cm –1 ) and α-FeOOH (615 cm –1 ). , Especially, a characteristic peak at 1512 cm –1 corresponding to the shear vibration of N–H was observed beneath PDA@EVA/EP, besides a broad adsorption peak exhibited around 3500–3000 cm –1 , ascribing to stretching vibration of catechol and secondary amino groups. , These observations proved the existence of PDA on the steel surface, supporting the possibility of PDA on inhibiting metal corrosion. Raman characterizations also were applied to investigate the corrosion products composition (Figure b), mainly involving γ-FeOOH (213 and 1308 cm –1 ), α-FeOOH (276 and 385 cm –1 ), and Fe 3 O 4 (691 cm –1 ). The presumable reaction process of different types of corrosion products generated beneath pure EP could be clarified as follows: The fast infiltration of aggressive species (such as O 2 , H 2 O, and Cl – ions) through the opened scratch channel resulted in the damage and dissolution of lots of generated Fe 2 O 3 (main component in Fe 3 O 4 ) (Figure b) .…”
Section: Resultsmentioning
confidence: 58%
“…68,69 Especially, a characteristic peak at 1512 cm −1 corresponding to the shear vibration of N−H was observed beneath PDA@EVA/EP, besides a broad adsorption peak exhibited around 3500−3000 cm −1 , ascribing to stretching vibration of catechol and secondary amino groups. 70,71 These observations proved the existence of PDA on the steel surface, supporting the possibility of PDA on inhibiting metal corrosion. Raman characterizations also were applied to investigate the corrosion products composition (Figure 10b), mainly involving γ-FeOOH (213 and 1308 cm −1 ), α-FeOOH (276 and 385 cm −1 ), and Fe 3 O 4 (691 cm −1 ).…”
Section: Adhesion Evaluation During the Healing Processmentioning
confidence: 55%
“…29,30 The remarkable adaptability, strong adhesion to substrates, environmentally friendly degradation, and self-healing capabilities make PDA a promising material for corrosion-resistant modification. Li et al 31 applied a PDA anticorrosion coating on the surface of N80 steel through PDA self-polymerization and assembly. They observed that the PDA coating exhibited excellent stability in produced water from oil wells and maintained stable anticorrosion performance under high-temperature conditions.…”
Section: Introductionmentioning
confidence: 99%